Scleral structure and biomechanics. (January 2020) - Boote, Craig; Sigal, Ian A.; Grytz, Rafael; Hua, Yi; Nguyen, Thao D.; Girard, Michael J.A.
Abstract: As the eye's main load-bearing connective tissue, the sclera is centrally important to vision. In addition to cooperatively maintaining refractive status with the cornea, the sclera must also provide stable mechanical support to vulnerable internal ocular structures such as the retina and optic nerve head. Moreover, it must achieve this under complex, dynamic loading conditions imposed by eye movements and fluid pressures. Recent years have seen significant advances in our knowledge of scleral biomechanics, its modulation with ageing and disease, and their relationship to the hierarchical structure of the collagen-rich scleral extracellular matrix (ECM) and its resident cells. This review focuses on notable recent structural and biomechanical studies, setting their findings in the context of the wider scleral literature. It reviews recent progress in the development of scattering and bioimaging methods to resolve scleral ECM structure at multiple scales. In vivo and ex vivo experimental methods to characterise scleral biomechanics are explored, along with computational techniques that combine structural and biomechanical data to simulate ocular behaviour and extract tissue material properties. Studies into alterations of scleral structure and biomechanics in myopia and glaucoma are presented, and their results reconciled with associated findings on changes in the ageing eye. Finally, new developments in scleral surgery and emerging minimally invasive therapies are highlighted that could offer new hope in the fight against escalating scleral-related vision disorder worldwide. Highlights: Reviews the state of the art in structural, biomechanical and in silico techniques for characterising the sclera. Presents a comprehensive view of physiological biomechanical loads on the sclera, including fluid pressures and eye movements. Discusses recent findings on scleral changes in ageing, glaucoma and myopia. Challenges current thinking about the relationship between scleral structure and biomechanical function. Summarises recent therapeutic breakthroughs and predicts future areas of progress.